A Platinum(II) Phenylphenanthroimidazole with an Extended Side‐Chain Exhibits Slow Dissociation from a c‐Kit G‐Quadruplex Motif. Issue 52 (18th November 2013) - Castor, Katherine J.; Liu, Zhaomin; Fakhoury, Johans; Hancock, Mark A.; Mittermaier, Anthony; Moitessier, Nicolas; Sleiman, Hanadi F.
Abstract A series of three platinum(II) phenanthroimidazoles each containing a protonable side‐chain appended from the phenyl moiety through copper(I)‐catalyzed azide–alkyne cycloaddition (CuAAC) were evaluated for their capacities to bind to human telomere, c‐Myc, and c‐Kit derived G‐quadruplexes. The side‐chain has been optimized to enable a multivalent binding mode to G‐quadruplex motifs, which would potentially result in selective targeting. Molecular modeling, high‐throughput fluorescence intercalator displacement (HT‐FID) assays, and surface plasmon resonance (SPR) studies demonstrate that complex 2 exhibits significantly slower dissociation rates compared to platinum phenanthroimidazoles without side‐chains and other reported G‐quadruplex binders. Complex 2 showed little cytotoxicity in HeLa and A172 cancer cell lines, consistent with the fact that it does not follow a telomere‐targeting pathway. Preliminary mRNA analysis shows that 2 specifically interacts with the ckit promoter region. Overall, this study validates 2 as a useful molecular probe for c‐Kit related cancer pathways.